GIS-Based Natural Disaster Vulnerability Mapping in Donggala Regency, Central Sulawesi Province - Risqa Permatasyara Mumin; Deno Ambar Arum; Apriadi Saputra; Djamal Adi Nugroho Uno (Universitas Negeri Gorontalo, 2026)
Donggala Regency has diverse morphology, encompassing coastal areas and complex hilly terrains. Geomorphological studies are essential for understanding landforms and assessing the potential for related natural disasters. This study aims to identify dominant landforms and assess natural disaster vulnerability, including landslides, tsunamis, and liquefaction, using a Geographic Information System (GIS)-based approach. The methods employed in this research include the analysis of topographic maps, satellite imagery, and a review of literature on geological conditions. The results indicate that coastal areas are highly vulnerable to tsunamis, while hilly regions are more susceptible to landslides.